uPAR EXPRESSION IN CANINE NORMAL PROSTATE AND WITH PROLIFERATIVE DISORDERS - Mariana Rodrigues Faleiro; Denise Caroline Toledo; Marcela M. Pinto Rodrigues; Renee Laufer Amorim; Luiz Augusto B. Brito; Adilson Donizeti Damasceno; Veridiana M. B. Dignani de Moura (Ciência Animal Brasileira, 2013)
Prostatic lesions such as prostatic intraepithelial neoplasia (PIN) and proliferative inflammatory atrophy (PIA) are studied in human and canine species due to their malignance potential. The plasminogen activator (PA) system has been suggested to play a central role in cell adhesion, angiogenesis, inflammation, and tumor invasion. The urokinase-type plasminogen activator receptor (uPAR) is a component of the PA, with a range of expression in tumor and stromal cells. In this study, uPAR expression in both canine normal prostates and with proliferative disorders (benign prostatic hyperplasia-BPH, proliferative inflammatory atrophy-PIA, prostatic intraepithelial neoplasia-PIN, and carcinoma-PC) was evaluated by immunohistochemistry in a tissue microarray (TMA) slide to establish the role of this enzyme in extracellular matrix (ECM) remodeling and in the processes of tissue invasion. A total of 298 cores and 355 diagnoses were obtained, with 36 (10.1%) normal prostates, 46 (13.0%) with BPH, 128 (36.1%) with PIA, 74 (20.8%) with PIN and 71 (20.0%) with PC. There is variation in the expression of uPAR in canine prostate according to the lesion, with lower expression in normal tissue and with BPH, and higher expression in tissue with PIA, PIN and PC. The high expression of uPAR in inflammatory and neoplastic microenvironment indicates increased proteolytic activity in canine prostates with PIA, PIN, and PC.